2014
DOI: 10.1016/j.immuni.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

A Single Subset of Dendritic Cells Controls the Cytokine Bias of Natural Killer T Cell Responses to Diverse Glycolipid Antigens

Abstract: SummaryMany hematopoietic cell types express CD1d and are capable of presenting glycolipid antigens to invariant natural killer T cells (iNKT cells). However, the question of which cells are the principal presenters of glycolipid antigens in vivo remains controversial, and it has been suggested that this might vary depending on the structure of a particular glycolipid antigen. Here we have shown that a single type of cell, the CD8α+ DEC-205+ dendritic cell, was mainly responsible for capturing and presenting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
125
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(137 citation statements)
references
References 38 publications
9
125
0
3
Order By: Relevance
“…2B). Moreover, using labeled a-GalCer, we observed that compared with CD8a 2 DCs, CD8a + DCs more efficiently incorporate a-GalCer in vivo, a finding in line with Arora et al (25) (Supplemental Fig. 2C).…”
Section: Cd8asupporting
confidence: 91%
See 1 more Smart Citation
“…2B). Moreover, using labeled a-GalCer, we observed that compared with CD8a 2 DCs, CD8a + DCs more efficiently incorporate a-GalCer in vivo, a finding in line with Arora et al (25) (Supplemental Fig. 2C).…”
Section: Cd8asupporting
confidence: 91%
“…In the mouse system, DCs in the spleen, an important site of immune responses to blood-borne Ag, are mainly composed of CD8a + DCs, a subset specialized in Ag crosspresentation, and of CD8a 2 DCs, a subset more efficient at presenting Ag on MHC class II (24). Recent findings indicated that CD8a + DCs are particularly potent to activate iNKT cells (25) and to trigger iNKT cell-based innate immune responses (26,27). These data, and the fact that CD8a + DCs excel in Ag crosspresentation, prompted us to actively deliver a-GalCer and Ag to CD8a + DCs in vivo.…”
mentioning
confidence: 99%
“…Administration of synthetic CD1d-restricted lipid agonists (typically αGalCer) in vivo has been shown to rapidly activate iNKT cells, as a result of lipid-CD1d complex presentation by CD8α + DCs [21,22]. Activated iNKT cells upregulate costimulatory molecules, including CD40L, and within a few hours release considerable quantities of different type 1 and type 2 cytokines that, in turn, activate NK cells and induce DC maturation [21,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Some data suggest that Th1 responses depend on prolonged antigenic stimulation of iNKT cells, and this may be due to several factors, including enhanced GSL chemical stability in vivo, more stable binding of the GSL to CD1d, or increased TCR affinity for the GSL complex with CD1d (17). Alternatively, GSLs may have differential effects on antigen-presenting cells (APCs), for example, by trafficking to different components of the cell and inducing the expression of different cell surface molecules that influence immunity (27).…”
Section: Gsl Activation Of Inkt Cells Alters the Immune Responsementioning
confidence: 99%